RADIATION-INDUCED TOXICITY IN BREAST CANCER PATIENTS TREATED WITH TRASTUZUMAB-BASED CHEMOTHERAPY - R. Yu. Karabut; A. V. Vazhenin; E. Y. Mozerova; M. M. Sarycheva; A. A. Lozhkov; A. Yu. Maksimovskaya; D. M. Timokhina (Сибирский онкологический журнал, 2021)
The aim of the study was to determine and analyze the most significant risk factors for developing cardiac, pulmonary and skin toxicities among patients who received concurrent radiation therapy and chemotherapy with trastuzumab.Material and methods. The study included 66 patients with histologically verified invasive intermediate or low-grade breast carcinoma, who received radiation therapy and chemotherapy with trastuzumab from 2018 to 2019. The average age of the patients was 53.1 ± 4.2 years. Locally advanced stage iii a and iii b breast cancer was the most common (52 %) followed by stage ii a and ii b cancer (36 %). The lvef of all patients was ≥50 %. All patients received neoadjuvant chemotherapy with anthracyclines and/or taxanes. Radiation-induced side effects were assessed using the rtog/eortc scoring criteria. Dose-volume histogram (dvh) of radiotherapy planning was matched to the quantec criteria.Results. Radiation-induced pulmonitis was observed in 2 patients within 2 to 6 months after the completion of radiation therapy. A 10 % reduction in lvef was observed in 3 patients, while a 20 % decrease in ef was not found. Long qt syndrome was observed in 3 patients, and it was accompanied by clinical manifestations in 2 patients. When evaluating the echo-cg protocols after treatment, normal lv diastolic function was recorded in 39 patients, moderate diastolic dysfunction (lv dd) in 27, and 1 patient had severe lv dd. When assessing the dose received by the lv myocardium, the excess of the average dose to the myocardium was present both on the left and on the right. Only in 16 % of cases, left myocardial irradiation met criterion v 25. Clinically, arrhythmias, unstable angina pectoris, and other manifestations of coronary artery disease were mostly observed among patients with left-sided breast cancer. Significant factors for the development of cardiotoxicity were left-sided breast cancer, previous chemotherapy with anthracyclines and/or taxanes, as well as myocardial doses. The occurrence of radiation pulmonitis did not show an obvious relationship with any factor, while the body mass index (bmi) of >30 was a significant factor for the occurrence of radiation-induced skin damage.Conclusion. The combination of radiation therapy and trastuzumab was associated with an acceptable risk of cardiotoxicity. Monitoring of the cardiovascular system parameters during treatment and detection of early signs of cardiotoxicity were shown to be of great importance.